الإثنولوجياومسألتا الإختلاف الإثني والجنسي وإنتاج المعرفة الأنثروبولوجيةفي الجزائر - زيان, محمد (Changement Social, 2018)
The aim of my intervention is to clarify the role of French ethnology and how to deal withtwo important topics: the first about women, or rather the relationshipbetween men and women, and the second dealingwith the Berber and Arab dichotomies and thus how to deal withtheircurrent issues today and theirrole in producinganthropologicalknowledge in Algeria, perhapsthesetwotopicsrepresent, in ourview, the starting point on which the seeds of teaching in anthropologyat the Algerian university have been developed, and crystallized more in the ethnologicalworks of Germain Tillion, Pierre Bourdieu and Lacoste Dujardin.